PENGARUH TIME BUDGET PRESSURE, KOMPLEKSITAS AUDIT, KOMPETENSI AUDITOR, DAN INTEGRITAS TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI PROVINSI BALIâ€ - Dewi Ni Luh Putu Rosita; Putra I Putu Deddy Samtika (Hita Akuntansi dan Keuangan, 2022)
This â€œstudy aims to examine the effect of time budget pressure, audit complexity, auditor competence and integrity on audit quality. This research was conducted at 13 Public Accounting Firms in Bali Province. The number of samples used as many as 66 respondents. The method of determining the sample is non-probability sampling with purposive sampling technique. The data was collected using a questionnaire. The data analysis technique used was multiple linear regression analysis. The results of the analysis showed that Time Budget Pressure and Audit Complexity had no significant effect on audit quality. Meanwhile, Auditor Competence and Integrity had a significant positive effect on auditâ€ quality.